Curcumin inhibits colorectal cancer progression by targeting PTBP1 and CDK2-mediated pathways - Zheng, Hao; Li, Shenglong; Wang, Ye; Su, Shuang; Wang, Yiheng; Wang, Fujing (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) remains a significant cause of cancer-related mortality worldwide. Curcumin, a natural polyphenol, has shown promise in targeting key cancer pathways, but its precise molecular mechanisms in CRC are not fully understood. This study investigates the anti-cancer mechanisms of curcumin on CRC progression, focusing on PTBP1 and CDK2 as critical regulators.MethodsThe expression of PTBP1 was assessed in clinical CRC samples and curcumin-treated cells via PCR and Western blot. Functional assays—including CCK8, colony formation, flow cytometry, Transwell migration/invasion, and apoptosis/autophagy staining—were conducted to evaluate curcumin’s effects. CDK2 was identified as a direct target using pull-down, kinase activity, and immunoprecipitation assays. CDK2 knockout models were used to validate curcumin’s effects in vitro and in vivo.ResultsCurcumin markedly downregulated PTBP1 expression, and suppressed CRC cell proliferation, migration, and invasion while promoting apoptosis and autophagy. Mechanistic analysis revealed direct inhibition of CDK2 by curcumin, disrupting the CDK2–c-MYC–PTBP1 regulatory axis. CDK2 knockout mimicked curcumin’s effects but reduced the cells’ sensitivity to the treatment. In vivo, curcumin significantly inhibited tumor growth and activated autophagy-related pathways.ConclusionsThis study uncovers a novel mechanism in which curcumin suppresses CRC progression by targeting the CDK2–c-MYC–PTBP1 axis. These findings provide compelling evidence for curcumin’s therapeutic potential and support further clinical investigation.